Discovery of two novel ALKBH5 selective inhibitors that exhibit uncompetitive or competitive type and suppress the growth activity of glioblastoma multiforme. (8th April 2022) - Takahashi, Hikaru; Hase, Hiroaki; Yoshida, Takuya; Tashiro, Junki; Hirade, Yoshihiro; Kitae, Kaori; Tsujikawa, Kazutake
Abstract: A group of RNA methylation enzymes is currently of interest as a new target for cancer therapy. Alpha‐ketoglutarate‐dependent dioxygenase B (AlkB) homolog 5 (ALKBH5) is an N 6 ‑methyladenosine (m 6 A) demethylation enzyme, and by high‐throughput screening from pure small molecule compounds, we identified two novel inhibitors, Ena15 and Ena21, against it. Each compound showed either uncompetitive or competitive inhibition for 2‐oxoglutarate (2OG). In addition, Ena21 had little inhibitory activity for fat mass and obesity‐associated protein (FTO), which is another N 6 ‑methyladenosine demethylation enzyme, while Ena15 enhanced the demethylase activity of FTO. The predicted binding poses of both compounds with the crystal structure of ALKBH5 (PDB ID: 4NRO) were comparable with these observations pertaining to the interaction of the 2OG catalytic site in this enzyme kinetics. Furthermore, either knockdown of ALKBH5 or inhibition with Ena15 or Ena21 inhibited cell proliferation of glioblastoma multiforme‐derived cell lines, decreased cell population in the synthesis phase of the cell cycle, increased m 6 A RNA level, and stabilized FOXM1 mRNA. Based on these results, Ena15 and Ena21 were found to be potential candidates that might help in further research into the biological function of ALKBH5. Abstract : Two novel small molecule inhibitors of ALKBH5, Ena15 and Ena21, were identified using high throughput screening. Ena15 and Ena21 showed uncompetitive and competitive inhibition for 2OG, respectively. Ena21 may interact with oligonucleotide product and/or substrate. Ena15 cell growth inhibitory activity may be affected by the ALKBH5 mRNA expression level.